PHYSICO-CHEMICAL CHARACTERISTICS OF THE ROOT EXUDATE OF MUSTARD SEEDLINGS RAISED FROM THE SEEDS STORED WITH ASPERGILLUS FLAVUS - R. N. SAO, N. P. SINHA AND B. K. PRASAD, A. KISHOR, R. N. SINGH, N. NARAYAN (Indian Phytopathology, 2002)
The electrical conductivity of the root exudate of the seedlings of mustard raised from Aspergillus flavus inoculated seeds proportionately increased with increase in per cent RH of storage and prolongation of the storage period. Similar trends were also observed for sugars, total free amino acids and the cations.